2003
DOI: 10.1021/op0300239
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Preparation of a Key Intermediate in the Synthesis of Roxifiban by Enzymatic Dynamic Kinetic Resolution on Large Scale

Abstract: Additional information is presented for the transformation of a kinetic resolution into a dynamic kinetic resolution of the isobutyl ester 5b to form the acid 2 in high yield and ee via the intermediacy of a thioester 6c, (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 20 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…While this study was under investigation, Pesti et al [12] reported the synthesis of the R-acid 2 with 80.4% yield and .99.9% ee after crystallization by following enzymatic hydrolysis. This attracted our attention to the use of thioethyl ester of (+) acid 2.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…While this study was under investigation, Pesti et al [12] reported the synthesis of the R-acid 2 with 80.4% yield and .99.9% ee after crystallization by following enzymatic hydrolysis. This attracted our attention to the use of thioethyl ester of (+) acid 2.…”
Section: Resultsmentioning
confidence: 93%
“…1) Hydrolysis by amano lipase P30; [4] 2) EtSH, DCC, DMAP, EtOAc; 3) amano lipase P30, NaH 2 PO 4 buffer, Me 3 N, triton X; [12] de. If we compare this value (58% de) with the starting acid (28% ee), it is clear that significant diastereomeric enrichment (30%) had occurred.…”
Section: Roxifiban Synthesis 4159mentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral oxygen‐containing heterocycles, such as isoxazolines, isoxazolidines,1 chromans,2 and dihydrobenzofurans,3 can be found in numerous natural products and biologically active compounds, and significant efforts have been directed towards the development of synthetic methods that are capable of providing facile access to these materials. In particular, O‐heterocycles bearing an amide moiety,4 such as roxifiban1c and erythrococcamide,2c,e exhibit pharmaceutically important activities (Figure 1). Related carboxylic acids, such as acivicin1d and raxofelast,3b,c have been used as biological tools for drug discovery and as key synthetic intermediates for the construction of more complex derivatives.…”
Section: Methodsmentioning
confidence: 99%
“…An ingenious combination of enzymatic hydrolysis of thioester coupled with a retro-Michael/Michael equilibrium with a mild base (trimethylamine) for racemization was employed to effect dynamic resolution for the synthesis of a key chiral pharmaceutical intermediate for the synthesis of a platelet glycoprotein receptor antagonist [50]. Hydrolysis of the racemic thioester 97 catalyzed by the lipase from Pseudomonas cepacia led to the R-acid 98.…”
Section: Scheme 28mentioning
confidence: 99%